Export of agricultural commodities from India: Performance and prospects - SURESH, A; MATHUR, V C (The Indian Journal of Agricultural Sciences, 2016)
Indian agricultural export has undergone significant changes during recent times. In this context, the present study has analysed the trend in exports of agricultural commodities from India, the changes in the comparative advantage, the Indian agricultural export scenario has witnessed during the past decade and the prospects for further boosting the agricultural export. There was significant rate of growth of export during the past decade; with wide difference across various commodity groups. The growth was 41.5% in case of guargum and other resins; 27% in meat and offals; 26.6% in case of meat and meat products; 24-25% in case of sugar and spices and 16.4% in case of cereals. The rate of growth was low in case of fish and marine products, tea and coffee. The differential trend growths have resulted in the changes in the composition of export. The study finds a significant increase in the share of export of cereals from (3.3 to 6.9%), guargum and other resins (1.0 to 7.5%), cotton (14.1 to 17.3%), spices (2.3 to 3.3%), and sugar (3.9 to 4.3%). On the other hand, the share has declined in some commodities- the notable one being fish and marine products (14.0 to 7.6%), fruits and nuts (6.1 to 3.5%) and coffee and tea (5.4 to 3.5%). The study has also analysed the comparative advantage of India’s exports, through revealed comparative advantage (RCA). The RCA was improving in case of cotton, maize, and certain fruits and vegetables over time, but declining in case of some spices, rice and wheat. In case of plantation based spices and other commodities, India is gradually losing its comparative edge, mainly to Asian countries. The study has so identified yield improvement through growth in total factor productivity (TFP) as a potential factor that would result in generation of exportable surpluses and boosting India’s export.